A study on the effectiveness of pharmacopuncture for chronic neck pain: A protocol for a pragmatic randomized controlled trial. Issue 31 (31st July 2020) - Park, Kyoung Sun; Lee, Yoon Jae; Lee, Jinho; Ha, In-Hyuk
Abstract: Background: Neck pain is a common musculoskeletal disorder that impacts individuals' daily life, and might sometimes lead to disability and increased medical costs. Pharmacopuncture combines acupuncture with herbal medicine, in which herbal extracts are administered on the acupoints. We designed a pragmatic randomized controlled trial (RCT) to compare the effectiveness of pharmacopuncture and physical therapy as a treatment for chronic neck pain. Methods: This study is a 2-armed, parallel, multi-center RCT. The participants will be randomly assigned to pharmacopuncture or physical therapy group to receive their respective 8-session treatments for 4 weeks. The primary outcome is the visual analogue scale of neck pain. Secondary outcomes is the Northwick Park questionnaire, visual analogue scale of radiating arm pain, numeric rating scale of the neck and arm bothersomeness, neck disability index, patient global impression of change, short form-12 health survey version 2, and 5-level EuroQol-5 dimension. Discussion: This is a protocol for a pragmatic RCT that would attempt to present evidence conducive to clinical decision or policy-making by investigating the effectiveness of pharmacopuncture therapy, a widely used approach in Korean medicine clinical practice, in comparison to the standard therapy. Abstract : Supplemental Digital Content is available in the text